What is 1 – cos(2x) equal to?

The expression 1 – cos(2x) can be simplified using a trigonometric identity. According to the double angle formula, we know that:

  • cos(2x) = 2cos²(x) – 1

Now, we can substitute this identity into our expression:

1 – cos(2x) = 1 – (2cos²(x) – 1)

Simplifying this further gives:

  • 1 – 2cos²(x) + 1 = 2 – 2cos²(x)

Factoring out a 2, we have:

1 – cos(2x) = 2(1 – cos²(x))

Now, we can use another identity which states that:

  • 1 – cos²(x) = sin²(x)

Therefore, we substitute this in:

1 – cos(2x) = 2sin²(x)

In conclusion, the expression 1 – cos(2x) simplifies to 2sin²(x). This identity is useful in various trigonometric applications, particularly in solving equations involving sine and cosine.

More Related Questions